The case of zero-tillage technology in Argentina - Trigo, Eduardo J.; Cap, Eugenio; Malach, Valeria; Villarreal, Federico (International Food Policy Research Institute, 2009)
Argentine agriculture has undergone significant transformations over the past three decades. After a long period of stagnant production and productivity, starting in the early 1970s, a number of independent but interconnected events fostered a new technological cycle that induced rapid growth in cereals and oilseeds production. Zero tillage and the introduction of genetically modified soybean varieties were key elements of this change, which has significantly increased global supplies of soybeans, an essential food and feed crop. In the process, it has elevated Argentina to a leading position across agricultural commodity markets. This transformation was the result of an innovative partnership scheme—involving farmers, researchers, extension workers, and private companies—that came together in the 1990s to promote zero tillage, a resource-conserving cultivation practice. This partnership deserves most of the credit for increasing the area under zero tillage from 300 thousand to 22 million ha, between 1991 and 2008. The adoption of zero tillage improved soil fertility by reversing decades of soil degradation, created an estimated 200,000 new farm jobs, and shocked the agricultural commodity markets with additional supplies that helped keep global food prices from escalating. This paper reviews the institutional process through which these changes came about. It goes on to estimate the benefits attributable to the adoption of zero tillage, not only to Argentine farmers, in terms of increased income, but also to world consumers, measured in terms of savings in food expenditures. Total benefits are estimated at 34 billion dollars.